Micro Business Development Strategy by Creating Business Identification Number (NIB) in Wonoayu District - Putra, Moch Zufar Irhab S; Fadil, Cholid; Imaningsih, Niniek (Unram Journal of Community Service, 2025)
Business development strategies play a crucial role in enhancing local economic growth and entrepreneurial potential. This study examines the implementation of Business Identification Number (NIB) registration as a strategic approach to business development in Wonoayu Village. The activity aims to analyze the impact of NIB registration on local businesses, identifying the challenges and opportunities associated with formal business recognition. Using a mixed-methods approach, the study conducted comprehensive surveys, interviews, and document analysis with local entrepreneurs and village officials. The findings reveal that NIB registration significantly contributes to business formalization, providing entrepreneurs with improved access to financial services, government support, and legal protection. Key challenges include limited awareness of registration processes, bureaucratic complexities, and initial registration costs. However, the benefits demonstrate substantial potential for business growth, including enhanced credibility, increased market opportunities, and simplified business operations. The study suggests targeted support mechanisms, including local government guidance, capacity-building workshops, and simplified registration procedures to maximize NIB registration benefits. These findings contribute to understanding the role of formalization in local economic development and provide practical insights for supporting small and medium enterprises in rural contexts. The research highlights the importance of strategic interventions that can transform informal businesses into recognized, sustainable economic entities.